2018
DOI: 10.1186/s40168-018-0599-9
|View full text |Cite
|
Sign up to set email alerts
|

Rock substrate rather than black stain alterations drives microbial community structure in the passage of Lascaux Cave

Abstract: BackgroundThe World-famous UNESCO heritage from the Paleolithic human society, Lascaux Cave (France), has endeavored intense microclimatic perturbations, in part due to high touristic pressure. These perturbations have resulted in numerous disturbances of the cave ecosystem, including on its microbial compartment, which resulted in the formation of black stains especially on the rock faces of the passage. We investigated the cave microbiome in this part of Lascaux by sampling three mineral substrates (soil, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 49 publications
3
44
1
Order By: Relevance
“…However, we did find significant differences among bacterial communities in terms of their occupied niches (i.e., air, rock, sediment, and water), not unlike Brannen-Donnelly and Engel (2015) who reported that bacterial community composition in cave streams and sediments differed at the class level. More recently, Alonso et al (2018) reported that mineral substrate was the most significant factor determining cave microbial diversity and structure. Other studies also showed that the bacterial communities associated with dripping water in the Heshang Cave in central China were mostly dominated by Proteobacteria , while Actinobacteria was the most dominant phyla in weathered rocks in the same cave (Yun et al, 2016a, b).…”
Section: Discussionmentioning
confidence: 99%
“…However, we did find significant differences among bacterial communities in terms of their occupied niches (i.e., air, rock, sediment, and water), not unlike Brannen-Donnelly and Engel (2015) who reported that bacterial community composition in cave streams and sediments differed at the class level. More recently, Alonso et al (2018) reported that mineral substrate was the most significant factor determining cave microbial diversity and structure. Other studies also showed that the bacterial communities associated with dripping water in the Heshang Cave in central China were mostly dominated by Proteobacteria , while Actinobacteria was the most dominant phyla in weathered rocks in the same cave (Yun et al, 2016a, b).…”
Section: Discussionmentioning
confidence: 99%
“…Man-made layout Fittings Tourism Microbial outbreaks Chemical treatments Pristine caves: (Alonso et al, 2018), whose walls correspond to the same Cognacien limestone sampled in the other caves. Microbial outbreaks in Lascaux have been described (Bastian, Alabouvette, Jurado, et al, 2009).…”
Section: Cavesmentioning
confidence: 99%
“… Lascaux samples were taken from the Shaft of the Dead Man (in the Diaclase) and the inclined plane in the Passage (Alonso et al, ), whose walls correspond to the same Cognacien limestone sampled in the other caves. Microbial outbreaks in Lascaux have been described (Bastian, Alabouvette, Jurado, et al, ). …”
Section: Introductionmentioning
confidence: 99%
“…A recent study carried out on SABs colonizing the passage of Lascaux Cave revealed that mineral substrates were important drivers structuring both the total (DNA) and the metabolically active (RNA) microbial communities, more so than the presence of black discoloration and the seasonality did [43].…”
Section: Community Assembly At the Mineral-air Interfacementioning
confidence: 99%